A 2D DEM-based approach for modeling water-induced degradation of carbonate rock. (February 2020) - Gu, Dong Ming; Huang, Da; Zhang, Wen Gang; Gao, Xue Cheng; Yang, Chao
Abstract: The mechanical characteristics of sedimentary rocks, such as carbonates, are highly sensitive to the influence of water. In carbonate-rich regions, rock failures induced by water corrosion have been widely reported, such as the collapse of cliffs and rockslides. In this study, a 2D model was built to investigate the time-dependent strength degradation of carbonate rocks under the influence of water. First, degradation laws for two types of bonds were derived based on the different behaviors of depositional and diagenetic cements in water. Then, via developing customized code using the Fish language, the degradation laws were coupled with UDEC to build the numerical procedure. Finally, the ability of the proposed model to reproduce the macroscopic short- and long-term behaviors of carbonate rocks under the influence of water was validated by comparing the numerical results with the lab observations and measurements. The results show that the presented procedure is capable of simulating the strength properties of carbonate rocks submerged in water for different time periods (uncoupled tests), as well as the lifetime (time-to-failure) of rocks in a chemo-mechanically coupled condition.